Analisis Wawasan Kebudayaan Pelajar di SMP Negeri 1 Padang terhadap Program Minang Sahari - Davin Khalif Jefri; Alief Hafizh Syahrin; Azka Mazaya Zahrany; Jessica Elvis Juanita; Keysha April Celianda (PT PUSTAKA CENDEKIA GROUP, 2024)
Minang sahari is a weekly cultural program aimed at introducing and preserving minangkabau culture among students. This program incorporates various elements of minangkabau culture, such as cuisine, music, dance, language, and literature. By actively involving students, Minang sahari aims to enhance understanding and appreciation of local culture as well as to foster a sense of pride in Minangkabau cultural heritage. This study aims to evaluate the effectiveness of the minang sahari program in introducing and preserving minangkabau culture among students. It is a descriptive observational study using questionnaires to collect and analyze data on respondents' knowledge. The questionnaires are distributed to students participating in the minang sahari program at SMP Negeri 1 Padang. In this study, the results showed that the majority of respondents had a good understanding of minangkabau customs and traditions, with 27 respondents (35.00%) rating their understanding as good, followed by 21 respondents (27.30%) rating it as very good. The most common level of knowledge among respondents about minangkabau customs and traditions was sufficient knowledge, with 47 respondents (61.00%), followed by 13 respondents (16.90%) who knew a lot and even participated. The most common level of contribution of the minang sahari program to respondents was significant contribution, with 29 respondents (37.70%), followed by contribution with 19 respondents (24.60%). The aspect of minangkabau culture that was most interesting to respondents was art and performances, with 54 respondents (70.10%), followed by knowledge of traditional food, with 41 respondents (53.20%). The most common suggestion for improving cultural awareness from respondents was to increase the number of cultural activities, with 47 respondents (61.00%), followed by organizing training and workshops, with 32 respondents (41.60%). The research conducted on students at SMP Negeri 1 Padang regarding the impact of the minang sahari program on minangkabau cultural awareness can be summarized as follows: The minang sahari program has provided students with a good and very good understanding of minangkabau customs and traditions. It has also given students sufficient knowledge and even significant participation in minangkabau customs and traditions. The program has had a substantial and contributory impact on students' cultural awareness. The aspects of culture that most interest students in the minang sahari program are art and performances, as well as traditional food. To further enhance students' cultural awareness, it is recommended that SMP Negeri 1 Padang increase the number of cultural activities and organize training or workshops.